PsycEXTRA Dataset 2011
DOI: 10.1037/e512592013-686
|View full text |Cite
|
Sign up to set email alerts
|

When less is more: Feedback, priming, and the pseudoword superiority effect

Abstract: The present study combined masked priming with electrophysiological recordings to investigate orthographic priming effects with nonword targets. Targets were pronounceable nonwords (e.g., STRENG) or consonant strings (e.g., STRBNG), that both differed from a real word by a single letter substitution (STRONG). Targets were preceded by related primes that could be the same as the target (e.g., streng -STRENG, strbng-STRBNG) or the real word neighbor of the target (e.g., strong -STRENG, strong-STRBNG). Independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The N400, on the other hand, is thought to reflect activity related to the mapping of whole‐word form representations onto semantic representations, at least in experiments using single words rather than sentences. Although the results of prior research suggest that feedback from frequency‐sensitive whole‐word representations can influence N250 amplitude (e.g., Massol, Midgley, Holcomb, & Grainger ; Midgley, Holcomb, & Grainger, ; Morris, Franck, Grainger, & Holcomb, ), the bulk of such lexical influences is expected to be seen in the beginning of the N400 time window.…”
mentioning
confidence: 94%
“…The N400, on the other hand, is thought to reflect activity related to the mapping of whole‐word form representations onto semantic representations, at least in experiments using single words rather than sentences. Although the results of prior research suggest that feedback from frequency‐sensitive whole‐word representations can influence N250 amplitude (e.g., Massol, Midgley, Holcomb, & Grainger ; Midgley, Holcomb, & Grainger, ; Morris, Franck, Grainger, & Holcomb, ), the bulk of such lexical influences is expected to be seen in the beginning of the N400 time window.…”
mentioning
confidence: 94%
“…Hence, when the N250 component appears, size and shape invariance have already been achieved, and this can be interpreted as further evidence of access to abstract orthographic representations. Recent research has shown that the N250 amplitude can also be modulated by lexical factors (Duñabeitia, Molinaro, Laka, Estévez, & Carreiras, 2009;Massol, Midgley, Holcomb, & Grainger, 2011;Morris, Franck, Grainger, & Holcomb, 2007), reflecting the interaction between prelexical bottom-up and lexical-semantic topdown representations (Morris et al, 2007).…”
mentioning
confidence: 99%
“…The N400 pronounceability effect we observed seems more in line with this interpretation. Pronounceable nonwords typically show larger N400s than words ( Massol et al, 2011 ). Therefore, if unpronounceable nonwords are autocorrected and treated as words, they should have smaller amplitude N400s compared to pronounceable nonwords.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we might expect group differences in N250 effects if pronounceability effects are tied to phonotactics. In addition, pronounceable nonwords show a larger N400 compared to fully unpronounceable nonwords (e.g, consonant strings) in hearing readers ( Massol et al, 2011 ). If this effect is driven by orthography, deaf and hearing readers should show similar N400 effects, but if it is driven by phonology, then deaf readers may show reduced or no modulation in N400 amplitude based on nonword pronounceability.…”
mentioning
confidence: 95%